Targeting Cell Metabolism in Chronic Lymphocytic Leukaemia (CLL); Aviable Therapeutic Approach? - E. Clapham Chloe; R. Pettitt Andrew; R. Slupsky Joseph (Journal of Hematology and Oncology Research, 2014)
Targeting cell metabolism is a therapeutic approach which has been used for the treatment of cancers with high levels of proliferation. Inhibition of metabolic processes in cancer cells has shown synergy with current therapeutic options to reduce refractory disease and relapse. In contrast, chronic lymphocytic leukaemia (CLL) is a disease where expansion of the malignant clone results from a combination of enhanced cell survival coupled with low level proliferation. The purpose of this article is to highlight how further research is needed to determine whether targeting cell metabolism may be a viable therapeutic strategy in this disease. We discuss how lymphocyte doubling time (LDT) remains a robust prognostic indicator used in the current clinical management of CLL, and how recognition of CLL as a proliferative disease has led to a greater understanding of the importance of energy-generating processes in its pathobiology. We summarize what is currently known about normal B cell metabolism and consider whether there is evidence of the Warburg effect in CLL cells. Finally, we speculate on how CLL cells may exploit protective mechanisms such as autophagy during times of metabolic stress and how they might influence or be influenced by metabolic characteristics of the microenvironment.
Keywords: Chronic lymphocytic leukaemia